Comparative analysis of the offensive effectiveness in winner and losing handball teams - Ferrari, W.; Dias, G.; Sousa, T.; Sarmento, H.; Vaz, V. (Frontiers in Psychology, 2020)
The purpose of this study was to determine differences related to the offensive process between winning and losing teams among teams participating in the European Handball Federation Champions League (EHFCL) in 55 matches across five seasons. The key indicators used in this study are the offensive actions, team possession type and the zones of the field, goals, and shooting effectiveness. A total of 34 indicators were analyzed and compared using Mann-Whitney U tests. Sixteen key indicators are identified to confirm differences both from the aspect of the collective game in terms of assists (9.10 ± 2.75 vs. 7.29 ± 2.65), goals of positional attack (21.38 ± 4.60 vs. 18.20 ± 3.62) and from the aspect of individual goals from 6 m (16.67 ± 3.98 vs. 13.64 ± 3.70), and the effectiveness of shots (68.19 ± 6.83 vs. 59.41 ± 6.33). Winning teams performed better regarding the variables that defined the effectiveness of offensive shots, especially successful positioned attacks and fast attacks. They also had a greater number of assists. The profiles of the most successful teams can help coaches and practitioners to achieve better performances adjusting the training process according the performance indicators that seem to lead more often to success.